Updated standardized catch rates of shortfin mako (Isurus oxyrinchus) caught by the Spanish surface longline fishery targeting swordfish in the Atlantic Ocean during the period 1990-2015 - Fernández-Costa, José; García-Cortés, Blanca; Ramos-Cartelle, Ana; Mejuto-García, Jaime (2017)
Standardized catches per unit of effort (in number and weight) were obtained for the shortfin mako (Isurus oxyrinchus) using General Linear Modeling procedures based on trip data from the Spanish surface longline fleet targeting swordfish in the North and South Atlantic Ocean over the period 1990-2015. A base case and two GLM sensitivity analyses were carried out including a MIXED procedure. Area was identified to be the most relevant factor in explaining CPUE variability in all cases. The base case models explained between 40-46% of CPUE variability. The comparison of the standardized CPUEs obtained from the base case and the sensitivity models show a very similar and stable general trend over time regardless of the model used for the North Atlantic stock. The base case and sensitivity analysis using a mixed model also show very similar trends over time in the case of the South Atlantic stock. All scenarios tested suggest overall stable CPUE trends or a slightly increase trend, in the North and South Atlantic stocks respectively.